Edukasi Program Promosi Kesehatan Melalui Media Video dan Poster - Dimas Eka Pratama; Totok Subianto; Ryan Gerry Patalo (Universitas Pendidikan Indonesia Kampus Purwakarta, 2022)
The condition of public compliance with health protocols that is getting lower has resulted in the increasing number of positive cases of the SARS-CoV-2 virus from day to day. The low level of community compliance is because the community has not fully accepted and implemented the health protocol rules. The purpose of this service is to provide education to the public about the importance of complying with health protocols during the Covid-19 pandemic. This service program is also expected to help the community to be independent in making health protocol equipment. The method of implementing this activity is by making video tutorials and posters for educational facilities and socialization of health promotion programs. The results of the videos and posters are distributed through social media channels because they are considered the right media for disseminating information widely and quickly.